Analisis Finansial Home Industry Roti Toris di Kelurahan Taratara Satu Kota Tomohon - Chyntia L.N. Rumampuk; Oktavianus Porajouw; Ribka M. Kumaat; Lyndon R.J. Pangemanan (COCOS, 2015)
ABSTRACT The objective of this research is to identify the costs, to analyze the advantages and financial feasibility of â€œTorisâ€ Bread home industry in Taratara SatuVillage, Tomohon Manucipality.The data were obtained by direct interviews with business owners, then analyzed by descriptive quantitativelyused calculation of Profit Analysis, Net Present Value (NPV), Internal Rate of Return (IRR), Net B/C Ratio, Payback Period (PP), and Break Even Point (BEP). The results showed net profit of â€œTorisâ€ Bread home industry was Rp 35,173,875 / year, it means Toris Bread home industry was profitable and feasible to be run. It is based on the financial feasibility analysis obtained by the value of the Net Present Value (NPV) obtained greater than zero, the Internal Rate of Return (IRR) is greater than the prevailing lending rate, the Net Benefit Cost Ratio (Net B/C ratio) isgreater than one, and the Payback Period (PP) founded that the returning of capitalduring 4 years 14 days, less than maximum target for 5 years. Keyword : Toris Bread home industry, Net Present Value (NPV)